Cerebral functional asymmetry and phonological performance in dyslexic adults. (7th October 2013) - Hernandez, N.; Andersson, F.; Edjlali, M.; Hommet, C.; Cottier, J. P.; Destrieux, C.; Bonnet‐Brilhault, F.
Abstract: Developmental dyslexia is a frequent language‐based learning disorder characterized by difficulty in reading. The predominant etiologic view postulates that reading impairment is related to phonological and orthographic dysfunction. The aim of this fMRI study was to evaluate the neural bases of phonological processing impairment in remediated dyslexic adults (DD). We used a rhyming words judgment task contrasted with an unreadable fonts font‐matching judgment task to compare patterns of activation and functional asymmetry in DD and normal‐reading young adults. We found evidence of a link between asymmetry in inferior frontal gyrus and performance during the phonological processing. We also observed that DD recruit a network including regions involved in articulatory control in order to achieve rhyme judgment suggesting that, due to a lack of hemispheric specialization, DD recruit the latter network to achieve rhyme judgment.